Productivity of the aberdeen-angus breed bred in different regions of the republic of kazakhstan - Nassambayev, E.; Akhmetalieva, A. B.; Nugmanova, A. E.; Batyrgaliyev, Y. A.; Kulbaev, R. (Ғылым және білім: мал шаруашылығы=Наука и образование: животноводство=Science and education: animal husbandry. - 2024. - № 1 (74). - Р. 26-33 (Uralsk)., 2024)
The article presents the genealogical structure, breed class composition of the herd, live weight of bulls-producers, cows, young stock, and milk yield of Aberdeen-Angus cows bred in different regions of the Republic of Kazakhstan, as well as the results of the study of the growth and development of young stock of the Aberdeen-Angus breed from 8 to 15 months of age for the last two years. The live weight of animals of meat breeds is the main indicator of meat productivity. Animals of the Aberdeen-Angus breed—bulls, producers, cows, and young stock at 8–15 months of age by live weight—in all age periods exceeded the requirements of the breed standard. At the same time, in 2023, there will be a decrease in the average daily gain compared to 2022. Farms need to pay attention to the issues of balanced feeding of young animals, applying feed additives, or using various feeds. Selection and directed breeding of animals with the best performance indicators and genetic potential allowed us to achieve stable parameters of animal productivity. In general, farms conduct systematic breeding work to improve the Aberdeen-Angus breed.
Keywords: Aberdeen-Angus breed; live weight; average daily gain; feed costs; milk yield; бқату; журнал кокснво; абердин-ангусская порода; крс; БҚАТУ; быки-производители